2010
DOI: 10.1103/physrevlett.105.046103
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Geometric and Electronic Relaxations at Organic-Metal Interfaces

Abstract: The correlation between the geometric and electronic structures of Zn-phthalocyanine (ZnPc) and F16ZnPc on Cu(111) were studied by x-ray standing wave and angle-resolved photoemission spectroscopy. We found evidence for a distortion of the planar molecules upon adsorption, with the central Zn atom in the molecule protruding towards the substrate. This modifies the energy levels of both the molecule and the substrate, which appear as interface states. The site-specific geometric and electronic relaxations are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 22 publications
3
54
0
Order By: Relevance
“…This fact indicates that the charge transfer governs the properties of this organometallic interface rather than structure effects as proposed in Ref. 21.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…This fact indicates that the charge transfer governs the properties of this organometallic interface rather than structure effects as proposed in Ref. 21.…”
mentioning
confidence: 52%
“…The different heights of the atoms relative to the substrate lower the symmetry upon adsorption. With vdW interaction we obtain atomic shifts of 0.31 Å for Zn and N, 0.43 Å for Zn and C, and 0.55 Å for Zn and H, while without vdW interaction we have 0.36 Å for Zn and N, 0.56 Å for Zn and C, and 0.71 Å for Zn and H. These values indicate that the molecular distortions are underestimated when the vdW interaction is included21. An increased molecule-substrate distance and flattened molecule, see Fig.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Additionally, several reports have shown that when Pc are adsorbed on metal surfaces the molecular plane will experience distortion and deformation. [45][46][47][48] By using X-ray standing waves, Yamane et al 46 reported that ZnPc is buckled on Cu(111), with the zinc center pulled towards the surface, and the carbon periphery also bending downwards compared to the central pyrrole nitrogen ring. Pre-fluorinated Pc (ZnPcF 16 and CuPcF 16 ) deform in the opposite direction on metal surfaces with the fluorine atoms facing the vacuum.…”
Section: Nexafsmentioning
confidence: 99%
“…Pre-fluorinated Pc (ZnPcF 16 and CuPcF 16 ) deform in the opposite direction on metal surfaces with the fluorine atoms facing the vacuum. [46][47][48] Thus, more theoretical and experimental work is needed to precisely determine the monolayer molecular configuration. At 3.8 ML, the line profiles in the π * region from the two polarizations resemble each other and are also consistent with previously reported results for ZnPc.…”
Section: Nexafsmentioning
confidence: 99%